Pengaruh Capital Intensity, Investment Opportunity Set dan Corporate Social Responsibility terhadap Konservatisme Akuntansi: Studi Empiris pada Perusahaan Food and Beverage yang Terdaftar di Bursa Efek Indonesia tahun 2018-2022 - Zelvira, Rahma; Honesty, Fiola Finomia; Honesty, Helga Nuri; Pebriyani, Dewi (Universitas Negeri Padang, 2024)
This study will examine the relationship between capital intensity, investment opportunities and corporate social responsibility on accounting conservatism. The scope of this research includes food and beverage companies with a total sample of 24 companies spanning a period of 5 years, namely from 2018-2022, so the total research sample is 120 food & beverage companies using a purposive sampling method based on certain criteria. The data in this research uses secondary data using the eviews analysis method. The research results show that capital intensity, investment opportunities and corporate social responsibility have no effect on accounting conservatism.